The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3889/oamjms.2017.096
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anterior Cruciate Ligament Remnant on Postoperative Clinical Results in Patients with Remnant Preserving Anterior Cruciate Ligament Reconstruction

Abstract: BACKGROUND:Anterior Cruciate Ligament (ACL) remnants have important biomechanical, vascular and proprioceptive function.AIM:To determine the influence of the ACL residual remnants after partial and complete ACL ruptures on postoperative clinical results in patients with remnant preserving ACL reconstruction.PATIENTS AND METHODS:The study included 66 patients divided into two groups. In patients from the investigation group remnant preserving ACL reconstruction was performed, in patients from the control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…A total of 284 citations were discarded because they were duplicates or did not fit the eligibility criteria. After full-text verification of the remaining 15 articles, seven studies with a combined 412 patients (208 in the remnant preservation technique group and 204 in the standard technique group) were included in the meta-analysis [ 17 23 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 284 citations were discarded because they were duplicates or did not fit the eligibility criteria. After full-text verification of the remaining 15 articles, seven studies with a combined 412 patients (208 in the remnant preservation technique group and 204 in the standard technique group) were included in the meta-analysis [ 17 23 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analysis was conducted to explore the possibility of heterogeneity in stability outcomes. The results showed that there was no particularly influential study among the included studies, except for the effects of the studies of Andonovski on side-to-side difference [ 23 ]. The mean follow-up time in this trial was 7 months.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, negating the requirement for autografts would theoretically solve troublesome donor site morbidity issues such as loss of hamstrings strength and anterior knee pain. Current practices and trends towards remnant preservation and some of the improvements shown in subjective proprioceptive outcomes, knee stability and revision rate (Takazawa et al 2013 ; Takahashi et al 2016 ; Muneta and Koga 2017 ; Andonovski et al 2017 ) can be extrapolated to offer hypothetical benefits for primary repair over reconstruction.…”
Section: Anterior Cruciate Ligament Injuriesmentioning
confidence: 99%
“…Over the last few years, with the recognition of the importance of tear type and tissue quality, there has been a renewed interest in arthroscopic primary ACL repair [ 20 , 24 , 41 , 43 ]. So, we noticed a crucial shift in favor of the preservation of the native ACL, even as a remnant in the cases of ACL reconstruction [ 49 ]. Kondo et al showed that remnant preservation in anatomic double-bundle ACL reconstruction significantly improved postoperative knee stability [ 50 ].…”
Section: Main Textmentioning
confidence: 99%
“…Kondo et al showed that remnant preservation in anatomic double-bundle ACL reconstruction significantly improved postoperative knee stability [ 50 ]. The importance of proprioception in knee stability and self-protection from a re-rupture led the orthopedic science to investigate new primary ACL repair techniques [ 49 , 50 ]. In a way, our findings suggest that orthopedic science has moved “back to the future” by rediscovering previous anterior cruciate ligament repair strategies couched in sophisticated, modernized surgical techniques of the twentieth-first century.…”
Section: Main Textmentioning
confidence: 99%